2020
DOI: 10.1007/s10926-020-09882-2
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Return to Work Self-efficacy for Return to Work Among Employees with Cancer Undergoing Chemotherapy

Abstract: The aim of the present study was to examine the predictive value of Return to Work Self-efficacy (RTWSE) on Return to Work (RTW) among employees undergoing chemotherapy for cancer and to examine the relative contribution of RTWSE as predictor variable compared to personal, health-related, illness-and treatment-related and work-related factors. Methods A sample of 114 sickness absent employees with various cancers (age 18-62) included in the study on average 33 days after initiating chemotherapy were followed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 52 publications
0
23
0
1
Order By: Relevance
“…The predictive power of RTW-SE on cancer survivors' RTW should be discussed. Rosbjerg et al (2020) suggested that RTW-SE does not appear as the strongest predictor of RTW among cancer patients undergoing chemotherapy. However, the small sample size of this study does not permit any generalisation of this result (Rosbjerg et al, 2020).…”
Section: G Ener Al-s E C An Cer Manag Ement-s E and Rt W-s Ementioning
confidence: 99%
See 2 more Smart Citations
“…The predictive power of RTW-SE on cancer survivors' RTW should be discussed. Rosbjerg et al (2020) suggested that RTW-SE does not appear as the strongest predictor of RTW among cancer patients undergoing chemotherapy. However, the small sample size of this study does not permit any generalisation of this result (Rosbjerg et al, 2020).…”
Section: G Ener Al-s E C An Cer Manag Ement-s E and Rt W-s Ementioning
confidence: 99%
“…Rosbjerg et al (2020) suggested that RTW-SE does not appear as the strongest predictor of RTW among cancer patients undergoing chemotherapy. However, the small sample size of this study does not permit any generalisation of this result (Rosbjerg et al, 2020). Among workers with psychological or upper-body musculoskeletal injuries, RTW-SE showed the strongest relationship with RTW (Black, Keegel, Sim, Collie, & Smith, 2018).…”
Section: G Ener Al-s E C An Cer Manag Ement-s E and Rt W-s Ementioning
confidence: 99%
See 1 more Smart Citation
“…In a non‐randomised study, Leensen et al (2017) found that participation in a multidisciplinary cancer rehabilitation programme seemed to improve both actual RTW and RTWSE, and Bains et al (2012) found job SE to be related to work status at baseline in an observational prospective study among patients with colorectal cancer. Furthermore, using the RTWSE‐11, Wolvers et al (2018) found RTWSE to be predictive of full RTW among cancer patients in curative care during 18 months follow‐up, whereas RTWSE was shown to be a less important predictor of actual RTW than other factors such as gender and treatment intention when measured with the RTWSE‐19 DK in a sample of cancer patients with various treatment intentions (Rosbjerg et al, 2020). These contradictory results may be related to differences between study samples and the use of different tools for measuring RTWSE in the two studies (Rosbjerg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using the RTWSE‐11, Wolvers et al (2018) found RTWSE to be predictive of full RTW among cancer patients in curative care during 18 months follow‐up, whereas RTWSE was shown to be a less important predictor of actual RTW than other factors such as gender and treatment intention when measured with the RTWSE‐19 DK in a sample of cancer patients with various treatment intentions (Rosbjerg et al, 2020). These contradictory results may be related to differences between study samples and the use of different tools for measuring RTWSE in the two studies (Rosbjerg et al, 2020). Besides being associated with work status and RTW in cancer populations, RTWSE has also been shown to be associated with factors which are correlated with RTW as well.…”
Section: Introductionmentioning
confidence: 99%